Global pentecostal and charismatic healing - Brown, Candy Gunther (Oxford Univ. Press, 2011)
Pentecostalism and the globalization of illness and healing / Candy Gunther Brown -- The global character of nineteenth-century divine healing / Heather D. Curtis -- Why health and wealth? : dimensions of prosperity among Swedish Charismatics / Simon Coleman -- Material salvation : healing, deliverance, and "breakthrough" in African migrant churches in Germany / Claudia Währisch-Oblau -- Blessed bodies : healing within the African American faith movement / Catherine Bowler -- Jesus as the great physician : Pentecostal Native North Americans within the Assemblies of God and new understandings of Pentecostal healing / Angela Tarango -- Latino Pentecostal healing in the North American Borderlands / Gastón Espinosa -- Santidad, salvación, sanidad, liberación : the word of faith movement among twenty-first century Latina/o Pentecostals / Arlene Sánchez Walsh -- Exorcising the demons of deprivation : divine healing and conversion in Brazilian Pentecostalism / R. Andrew Chesnut -- The salve of divine healing : essential rituals for survival among working-class Pentecostals in Bogotá, Colombia / Rebecca Pierce Bomann -- Learning from the master : Carlos Annacondia and the standardization of Pentecostal practices in and beyond Argentina / Matthew Marostica -- New wine in an old wine bottle? Charismatic healing in the mainline churches in Ghana / Cephas N. Omenyo -- Healing in African Pentecostalism : the "victorious living" of David Oyedepo / Paul Gifford -- Reenchanted : divine healing in Korean Protestantism / Sean C. Kim -- Miracle healing and exorcism in South Indian Pentecostalism / Michael Bergunder -- Divine healing and the growth of practical Christianity in China / Gotthard Oblau -- Catholic charismatic healing in global perspective : the cases of India, Brazil, and Nigeria / Thomas J. Csordas -- Global awakening : divine healing networks and global community in North America, Brazil, Mozambique, and beyond / Candy Gunther Brown
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Wunderheilung; Geistheilung; Charismatische Bewegung; Pfingstbewegung